Funnel-shaped fluid-escape structure: a clastic dyke complex formed by multiple, discrete fluidizations - Son, Junghee; Hwang, In Gul (Frontiers in Earth Science, 2025)
This study presents a remarkably well-preserved funnel-shaped fluid-escape structure exposed within the Hakcheon–Chogok Megaturbidite of the Doumsan fan-delta, Southeast Korea. Detailed sedimentological observations indicate that the structure represents a clastic dyke complex formed through multiple, discrete fluidization events. These events are inferred to have been triggered by repeated instantaneous loadings associated with mass-transport processes at the base of steeply inclined (15°–30°) depositional slopes during fan-delta evolution. A key factor controlling the formation and evolution of the structure was the localized enrichment and infiltration of fine-grained sediments (<0.25 mm) in both the lower conglomeratic unit (pebble-rich conglomerate) and the overlying sand–mud unit (coarse sandstone to mudstone). This spatial variation facilitated selective infiltration between the two units, producing localized low-permeability barriers that promoted overpressure buildup and vertical fluid migration. Cross-cutting relationships and compositional contrasts among internal dyke-like structures define at least three distinct phases of fluidization: (Phase I) initial propagation of dendritic granule-rich dykes, stabilized by effective infiltration of fine-grained sediments; (Phase II) intrusion of fine sand-rich dykes accompanied by ductile deformation and conduit instability due to insufficient wall infiltration; and (Phase III) lateral migration of faint, medium sand-dominated pipes that crosscut earlier structures and generated massive sand bodies. Despite this lateral migration and instability, the left margin displays a sharp boundary and narrow fluidization halo, indicating localized infiltration along the dyke wall. The occurrence of fine-depleted pipes in the lower unit is interpreted to record partial fluidization and elutriation that redistributed fine particles along pre-existing pathways. This redistribution is interpreted to have reinforced previously fluidized zones and promoted subsequent fluidization at similar positions. These results demonstrate that the spatial distribution and dynamics of fine-grained sediments critically governed overpressure development, conduit morphology, and internal asymmetry of the funnel-shaped structure, providing new insights into sediment–fluid interactions and the formation of large-scale clastic intrusions within coarse-grained turbiditic systems.